ANALISIS KUALITATIF PELAYANAN DAN KINERJA KEUANGAN PADA MASA COVID 19 DI RSUD DR. SAIFUL ANWAR MALANG - Rintan Nurulita Arofi; Dwiyani Sudaryanti; Siti Aminah Anwar (Universitas Islam Malang, 2022)
The purpose of this study was to analyze the quality of service and financial performance during the covid 19 period at Dr. RSUD. Saiful Anwar Malang. On financial performance through analysis of profitability ratios and liquidity ratios. The model in the research conducted is through field research and analyzing financial statements to determine the level of comparison of profitability ratio analysis and liquidity ratios during the covid 19 period. The results of this study indicate that to analyze the quality of service during the covid 19 period, many changes have occurred. To analyze financial performance in the calculation of profitability ratios which include return on assets and return on equity, it can be seen from the three cash flows from operating activities that present hospital income and expenses which have increased and decreased in 2019 and 2020. In the calculation of the liquidity ratio which includes The current ratio can be seen from the number of current assets/current assets and short-term liabilities in 2019 and 2020, showing that financial performance has decreased from 2019 to 2020 and can be said to be good.Keywords: Service Quality, Profitability Ratio Analysis, Liquidity Ratio Analysis and Financial Performance.